Hydrodynamics drives shifts in phytoplankton community composition and carbon-to-chlorophyll a ratio in the northern South China Sea - Chen, Dawei; Shi, Zhen; Li, Ruihuan; Li, Xiangfu; Cheng, Yuanyue; Xu, Jie (Frontiers in Marine Science, 2023)
Phytoplankton play significant roles in the carbon cycle in oceans. Phytoplankton biomass and community composition are often mediated by ocean hydrodynamics. It is vital to quantify the phytoplankton carbon content and carbon:Chlorophyll a (C:Chl a) ratio and to better understand the link between hydrodynamics and phytoplankton communities in marine environments, which are important parameters in marine biogeochemical models. Environmental variables, phytoplankton community composition, abundance, particulate organic carbon, and Chl a were determined in summer in the northern South China Sea (SCS), which was influenced by the Pearl River discharge, upwelling, and anticyclonic eddy, to examine the links between hydrodynamics, phytoplankton community, and C:Chl a ratio. Our results showed that the spatial variabilities in phytoplankton community composition, and carbon content, and C:Chl a ratio were driven by hydrodynamics. Nutrient enrichment favored the growth of diatoms, especially small chain-forming diatoms at the Pearl River Estuary stations. From inshore to offshore, the dominant phytoplankton shifted from small-chain diatoms to large diatoms and dinoflagellates, increasing phytoplankton biodiversity from inshore to offshore. Weak upwelling caused an increase in Synechococcus abundance, while an anticyclonic eddy resulted in a high abundance of Prochlorococcus and Trichodesmium spp. in the present study. We found that the relationship between phytoplankton carbon content and the logarithm of Chl a concentration fit an exponential curve. The C:Chl a ratio increased from 72.7 g g−1 at Pearl River Estuary stations, to 101 g g−1 at Pearl River discharge dilution stations and to 131 g g−1 at SCS surface stations due to shifts in phytoplankton community composition. The low C:Chl a ratio was attributed to the high abundance of diatoms in the Pearl River plume-impacted area, whereas a high C:Chl a ratio was related to the dominance of cyanobacteria at SCS surface stations. Our findings provide insights into quantifying phytoplankton carbon content and understanding the links between hydrodynamics, phytoplankton community composition, carbon content, and C:Chl a ratio in oceans.